Determination of Recent Growth Hormone Abuse Using a Single Dried Blood Spot. (6th January 2020) - Reverter-Branchat, Gemma; Bosch, Jaume; Vall, Jessica; Farré, Magí; Papaseit, Esther; Pichini, Simona; Segura, Jordi
Abstract: BACKGROUND: Although it is being increasingly applied, blood collection for drug testing in sport presents some logistic issues that complicate full applicability on a large scale. The use of dried blood spots (DBS) could benefit compliant blood testing considerably owing to its simplicity, minimal invasiveness, analyte stability, and reduced costs. The aim of this study was to evaluate the applicability of DBS to the methodology approved by the World Anti-Doping Agency (WADA) for detection of doping by recombinant human growth hormone (rhGH) in serum. METHODS: A protocol for a single DBS analysis using the hGH isoforms differential immunoassays (kit 1 and kit 2) was developed and validated. A clinical study with healthy volunteers injected for 3 consecutive days with a low subcutaneous dose (0.027 mg · kg −1 · day −1 · person −1 ) of rhGH was conducted. Finger prick DBS and paired-time serum samples from arm venipuncture were compared. RESULTS: The analysis of the DBS-based protocol indicated that with only a single blood spot it was possible to detect positivity for growth hormone abuse. In spite of the low rhGH dose administered and independently of the kit used, the window of detection for DBS was confirmed in all analyzed samples up to 8 h after rhGH administration and extended up to 12 h in 50% of the cases. Serum positivity was detected in all studied samples for 12 h after administration. CONCLUSIONS: These results support the usefulness of DBS as a biological matrix for testing recent growth hormone abuse.